Tingkat Kepercayaan Diri Anggota Ekstrakurikuler Futsal SMAN 4 Madiun - Arif Utomo; Ananda Perwira Bakti; Pudjijuniarto Pudjijuniarto; Mukhamad Nur Bawono (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
Futsal is a sport with a team system which is very popular among Indonesian people, especially men. This can be seen from the many futsal competitions from early childhood, student, student, general and amateur to professional levels. Futsal competitions at student level involve teams from schools to show their best game. There are many factors that can influence a player's performance on the field, one of which is self-confidence. Self-confidence is a person's belief in their own ability to achieve goals or face challenges. The level of self-confidence is influenced by internal and external factors. It is not possible for a person to immediately gain high self-confidence, but it is necessary to practice and increase the number of hours of competition to increase a person's maximum level of self-confidence. This research was motivated by researchers who wanted to know the level of self-confidence of futsal extracurricular members at SMAN 4 Madiun. The results of this research obtained a mean of 78.96, a median value of 78, a mode value of 75 and a standard deviation value of 11.197. Also obtained was a minimum score of 59 and a maximum score of 104. So it can be concluded that the futsal extracurricular members of SMAN 4 Madiun have a level of self-confidence in the "High" category. With these results, the futsal extracurricular members of SMAN 4 Madiun were declared able to display their best performance in the match without hesitation and full of confidence.